2002
DOI: 10.3189/172756502781831089
|View full text |Cite
|
Sign up to set email alerts
|

The retreat of a tidewater glacier: observations and model calculations on Hansbreen, Spitsbergen

Abstract: Based on observations and model calculations, the retreat over the last two decades of Hansbreen, a tidewater glacier in southern Spitsbergen, Svalbard, is investigated. The observations of the calving-front position between 1982 and 1998 show an abrupt retreat in 1990, which is suggested to be related to a depression in the glacier bed. The observed seasonal variations of the front position are mainly due to variations of the calving rate. The observations of Hansbreen further indicate that during periods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(148 citation statements)
references
References 29 publications
(65 reference statements)
6
135
1
6
Order By: Relevance
“…Locations where the Ecology Glacier ice front position was relatively stable and the retreat rate was low coincide with a presence of the bedrock outcrops (Figure 10), indicating that the glacier retreat may be governed by the presence of pinning points [58]. Despite shallow depths of the proglacial lagoon, it seems that the water depth controls termini retreat rate through enhanced calving.…”
Section: Discussionmentioning
confidence: 99%
“…Locations where the Ecology Glacier ice front position was relatively stable and the retreat rate was low coincide with a presence of the bedrock outcrops (Figure 10), indicating that the glacier retreat may be governed by the presence of pinning points [58]. Despite shallow depths of the proglacial lagoon, it seems that the water depth controls termini retreat rate through enhanced calving.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum rates, although high, are still several times below the typically observed calving rates, suggesting that basal melt must rather act through changing the shape of the front thereby influencing the stress field, such as through undercutting, and consequently affecting the calving rates (Rignot et al 2010;Motyka et al 2002;Vieli et al 2002). This provides a major challenge for forcing ice flow models with ocean data as it is in this case unclear how to link ocean melt rates to the process of calving.…”
Section: Oceanic Forcingmentioning
confidence: 99%
“…For Hansbreen, Spitsbergen, the time scales of the modelled fast retreats over bed depressions correspond well with observed retreat rates (Vieli et al 2002). Nick et al (2007) applied a simplified model to Columbia Glacier, Alaska, and confirmed the importance of bed geometry for calving rates, especially if moraines modify the bed topography near the calving front.…”
Section: Grounded Icementioning
confidence: 87%
“…A few grounded calving fronts have been observed over time periods of decades, such as Columbia Glacier, Alaska (Krimmel 2001) and Hansbreen, Spitsbergen (Vieli et al 2002). These observations clearly reveal a connection between the calving rate and resulting advance or retreat rates and the bed geometry (Van der Veen 1996).…”
Section: Grounded Icementioning
confidence: 89%
See 1 more Smart Citation